Liofilchem(®) O.A. Listeria agar and direct CAMP test provided sooner Listeria monocytogenes identification from neonatal bacteremia - Savini, Vincenzo (e-Century Publishing Corporation, 2014)
Listeria monocytogenes infection in pregnant women and newborns is a cause for serious concern, and invasive disease outcome strongly depends on prompt antibiotic therapy. To provide sooner identification from neonatal bacteremia we performed a CAMP test directly on positive blood aliquots and inoculated the Liofilchem(®) O.A. Listeria chromogenic agar as well, thus providing a 24-h turn-around time for response.